Mortality reduction and cost-effectiveness of performing hysterectomy at the time of risk-reducing salpingo-oophorectomy for prophylaxis against serous/serous-like uterine cancers in BRCA1 mutation carriers - Havrilesky, Laura J.; Moss, Haley A.; Chino, Junzo; Myers, Evan R.; Kauff, Noah D. (Gynecologic oncology, 2017)
To estimate the survival benefit and cost-effectiveness of performing hysterectomy during risk-reducing salpingo-oophorectomy (RRSO) for BRCA1 mutation carriers. Based on a recent prospective cohort study indicating an elevated incidence of serous/serous-like uterine cancers among BRCA1 mutation carriers, we constructed a modified Markov decision model from a payer perspective to inform decisions about performance of hysterectomy during RRSO at age 40. We assumed patients had previously undergone a risk-reducing mastectomy and had a residual risk of death from breast or ovarian cancer. Disease-specific survival, age-adjusted competing hysterectomy rates, and deaths from other causes were incorporated. Costs of risk-reducing surgery, competing hysterectomy, and care for serous/serous-like uterine cancer were included. A 40year old woman who undergoes RRSO+Hysterectomy gains 4.9 additional months of overall survival (40.38 versus 39.97 undiscounted years) compared to RRSO alone. The lifetime probabilities of developing or dying from serous/serous-like uterine cancer in the RRSO group are 3.5% and 2%, respectively. The RRSO alone strategy has an average cost of $9013 compared to $8803 for RRSO+Hysterectomy, and is dominated (less effective and more costly) when compared to RRSO+Hysterectomy. In an alternative analysis, delayed hysterectomy remains a cost-effective prevention strategy with an ICER of less than $100,000/year for up to 25years following RRSO at age 40. The addition of hysterectomy to RRSO in a 40year old BRCA1 mutation carrier results in a mean gain of 4.9 additional months of life and is cost-effective. •A cost-effectiveness model compared RRSO+/−hysterectomy for BRCA1 mutation carriers.•RRSO+immediate hysterectomy is more effective and less costly than RRSO.•Delayed risk-reducing hysterectomy is cost-effective for up to 25years after RRSO.